Do natural disasters stimulate individual saving? Evidence from a natural experiment in a highly developed country - Michael Berlemann; Max Steinhardt; Jascha Tutt (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
While various empirical studies have found negative growth-effects of natural disasters, little is yet known about the microeconomic channels through which disasters might affect short- and especially long-term growth. This paper contributes to filling this gap in the literature by studying how natural disasters affect individual saving decisions. This study makes use of a natural experiment created by the European Flood of August 2002. Using micro data from the German Socio-Economic Panel that we combine with geographic flood data, we compare the savings behavior of affected and non-affected individuals by using a difference-in-differences approach. Our empirical results indicate that natural disasters depress individual saving decisions, which might be the consequence of a Samaritan's Dilemma.
Keywords: Q54; D14; O16; H84; 330; natural disasters; floods; growth; saving behavior; difference-in-differences approach